PENGARUH KOMPETENSI DAN INTEGRITAS TERHADAP PENCEGAHAN KECURANGAN DENGAN PENGENDALIAN INTERNAL SEBAGAI VARIABEL MEDIASI - Muhammad Ramadhan Arif; Sukrisno Agoes (Jurnal Kontemporer Akuntansi, 2024)
This study aims to analyze the effect of competence, integrity, and experience on fraud prevention with internalcontrol as a mediating variable. This study uses internal auditors as the object of research. The data used areprimary data in the form of questionnaires distributed to internal auditors who work at commercial propertycompanies. There are 81 questionnaires were distributed to respondents and 73 returned. This study used aquantitative approach and used multiple linear regression analysis with additional validity and reliability tests. Thisstudy also uses hypothesis testing in the form of t statistic test and coefficient of determination test. The results ofthis study indicate that competence, integrity and internal control have an effect on fraud prevention, while theexperience variable has no effect on fraud prevention, and integrity has no effect on internal control, for competenceand experience variables have no effect on internal control.